Features of change of intracardiac gemodynamics and functional state of myocardium under the impact of telmisartan in patients with hypertension. - V. I. Koshlia; M. Ben-Abid (Medičnì Perspektivi)
In 41 patients with essential hypertension I and II degrees telmisartan influence on parameters of intimate heodynamics and functional condition of myocardium ofLVhas been studied. Carried out researches have shown, that on a background of treatment with telmisartan reduction of final diastolic volume of LV, final systolic meredional stress and final diastolic pressure of the myocardium and increase in fraction of LV ejection emission and speed of circular reduction of myocardium fibres is marked. The specified changes may be explained by improvement of plastic characteristics of the myocardium that is caused both by direct action of telmisartan on the myocardium through blockade of a local renin-angiotensin- aldosterone system, and by the mediated influence due to decrease of blood pressure and after post loading.